Case report: Application of non-VKA oral anticoagulants in patient of idiopathic hypereosinophilic syndrome with intracardiac thrombus - Zou, Man; Liu, Geyan; Li, Yanhui (Frontiers in Pharmacology, 2022)
Idiopathic hypereosinophilic syndrome (IHES) is a rare but life-threatening disease related to a group of myeloproliferative disorders characterized by prolonged eosinophilia of unknown cause and inflammatory damage to multiple organs. Here, we present a 44-year-old female patient complaining of shortness of breath and palpitations for one month. Her history and presentation were unremarkable, except for a 3-year history of rheumatoid arthritis treated with ibuprofen (0.3 g per day). Initial examination showed heart rate (HR) 120 bpm, respiratory rate (RR) 20 bpm, temperature (T) 36 °C, blood pressure (BP) 130/70 mmHg, ventricular gallop rhythm, rales at the lung bases, soft abdomen, nonpalpable liver and spleen, and slight edema in both lower extremities. Bone marrow aspirate and biopsy confirmed the diagnosis of IHES, while cardiac MRI showed intracardiac thrombus. The symptoms of shortness of breath and palpitation disappeared, the eosinophil counts in routine blood tests were normal, and the thrombus in the cardiac cavity gradually disappeared after combined therapy of anti-hypereosinophilic, anti-coagulant and anti-heart failure treatments.